Paradigms of Knowledge Management With Systems Modelling Case Studies - Pandey, Krishna Nath.; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2016)
This book has been written by studying the knowledge management implementation at POWERGRID India, one of the largest power distribution companies in the world. The patterns which have led to models, both hypothesized and data-enabled, have been provided. The book suggests ways and means to follow for knowledge management implementation, especially for organizations with multiple business verticals to follow. The book underlines that knowledge is both an entity and organizational asset which can be managed. A holistic view of knowledge management implementation has been provided. It also emphasizes the phenomenological importance of human resource parameters as compared to that of technological parameters. Various hypotheses have been tested to validate the significant models hypothesized. This work will prove useful to corporations, researchers, and independent professionals working to study or implement knowledge management paradigms.
Introduction -- The Context -- The Description of The Case (Powergrid) -- Research Methodology -- Data Collection, Analysis and Interpretation -- Discussion and Conclusion -- Appendices -- Bibliography. .
Keywords: Security systems; Knowledge management; Industrial Management; Security Science and Technology; Knowledge Management; Industrial Management